Revision of Municipal Development Charges in Portugal: contributions to a new urban paradigm - Emília Malcata Rebelo (2014)
This communication fits into the overall structural reform of the legislation that frames the territorial planning and urban development currently taking place in Portugal. This reform aims at strengthening a new urban paradigm, providing the legal support to policy development and implementation in more equitable, flexible, transparent and sustainable ways. Within this scope, this communication presents a proposal to reformulate the Portuguese Municipal Development Charges. This revision is crucial within the current socio-economic crisis that strongly shapes municipal finances, and expresses the concern to provide municipalities with sustainable tools in order to fight for the rights of their citizens. It is applied, as a case study, to the municipality of Bragança. This reassessment of municipal development charges fits the goals of the structural legal reform underway, and is deeply important for territorial development processes and for populationsŽ well-being as it warrants: (a) a greater resilience in the use of urban land, (b) the economic and financial sustainability of urban operations through a proper funding of development infrastructures; (c) higher transparency in the use of public funds; and (d) an increased fairness in the distribution of development costs and benefits among the population.